Training in Ultrasound to Determine Gestational Age (TUDA): Evaluation of a Novel Education Package to Teach Ultrasound-Naive Midwives Basic Obstetric Ultrasound in Malawi - Viner, Alexandra C.; Membe-Gadama, Gladys; Whyte, Sonia; Kayambo, Doris; Masamba, Martha; Makwakwa, Enita; Lissauer, David; Stock, Sarah J.; Norman, Jane E.; Reynolds, Rebecca M.; Magowan, Brian; Freyne, Bridget; et al. (Frontiers in Global Women's Health, 2022)
Introduction Although ultrasound to determine gestational age is fundamental to the optimum management of pregnancy and is recommended for all women by the World Health Organisation, it remains unavailable to many women in low-income countries where trained practitioners are scarce. This study aimed to evaluate a novel, context-specific education package to teach midwives basic obstetric ultrasound, including the determination of gestational age by measurement of fetal femur length. Methods The study was conducted across six sites in Malawi in January 2021. Following a virtual ‘training of the trainers’, local teams delivered a 10-day programme encompassing both didactic and ‘hands on’ components. Matched pre and post course tests assessed participants’ knowledge of key concepts, with Objective Structured Clinical Examinations used to evaluate practical skills. To achieve a pass, trainees were required to establish the gestational age to within +/- 7 days of an experienced practitioner and achieve an overall score of >65% on 5 consecutive occasions. A matched pre and post course survey explored participants’ attitudes and confidence in performing ultrasound examinations. Results Of the 29 midwives who participated, 28 finished the programme and met the criteria specified to pass. 22 midwives completed the matched knowledge tests, with the mean (SD) score increasing from 10.2(3.3) to 18(2.5) after training (P<0.0001). Mean difference 7.9, 95% CI 6.5-9.2. Midwives passed 87% of the Observed Structured Clinical Examinations, establishing the gestational age to within +/- 7 days of an experienced practitioner in 89% of assessments. Beliefs regarding the importance of antenatal ultrasound increased post course (p=0.02), as did confidence in performing ultrasound examinations (p <0.0001). Conclusion This study demonstrates not only that ultrasound-naive practitioners can be taught to perform basic obstetric ultrasound dating scans, confidently and competently, after 10 days of training, but also that local teams can be orientated to successful deliver the programme virtually. Previous ultrasound training initiatives, while often more comprehensive in their syllabus, have been of considerably longer duration and this is likely to be a barrier to upscaling opportunities. We propose that this focussed training increases the potential for widescale and sustainable implementation.